Assessment of the feed additive consisting of endo‐1,4‐beta‐xylanase (produced with Trichoderma reesei MUCL 49755) and endo‐1,3(4)‐beta‐glucanase (produced with T. reesei MUCL 49754) (AveMix® XG 10) for laying hens and minor poultry species for fattening and laying for the renewal of its authorisation (AVEVE BV) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the assessment of the feed additive consisting of endo‐1,4‐beta‐xylanase (produced with Trichoderma reesei MUCL 49755) and endo‐1,3(4)‐beta‐glucanase (produced with T. reesei MUCL 49754) (AveMix® XG 10/AveMix® XG 10 L) for the renewal of its authorisation as a zootechnical feed additive for laying hens and minor poultry species for fattening and laying. The applicant declared a change in the carrier material used in AveMix® XG 10 from soybean meal to calcium carbonate + wheat flour or calcium carbonate + sepiolite. The applicant provided evidence that the additive AveMix® XG 10 with calcium carbonate + wheat flour and AveMix® XG 10 L comply with the conditions of the authorisation. The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) noted that no data were submitted to support compliance of the formulation of AveMix® XG 10 with calcium carbonate + sepiolite with the conditions of the authorisation. The FEEDAP Panel concluded that both formulations of the additive (powder and liquid) remain safe for laying hens and minor poultry species for fattening and laying, consumers and the environment. AveMix® XG 10 formulated with calcium carbonate + sepiolite and AveMix® XG 10 L are not irritant to skin and eyes. No conclusions on the irritation potential of AveMix® XG 10 formulated with calcium carbonate + wheat flour could be drawn. The additive in both formulations is considered a respiratory and skin sensitiser. There was no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.